Leadless cardiac pacemaker in elderly patients: How old for a new technology?. (19th May 2022) - Ben Kilani, M; Carabelli, A; Jacon, P; Venier, S; Peter, P; Deschamps, E; Desbiolles, A; Defaye, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Leadless transcatheter pacemakers are considered as a safe and effective option for cardiac pacing in patients (pts) at higher risk of complications with conventional transvenous cardiac pacing. Purpose: Our aim was to assess the clinical "real-life" feasibility and outcomes of leadless pacing in elderly pts in a high-volume center over a mid-term follow-up (FU) period. Methods: Elderly pts (aged ≥ 75 years) who underwent leadless MICRA® system pacemaker implantation with a FU period above 3 months were included in this retrospective monocentric study. Results: 130 pts were included (84 ± 5.6 years old, male 66.2%). Indications were: Atrioventricular block (permanent 15.4%; transient 27.7%), atrial fibrillation bradycardia 50% and sinus node dysfunction 6.9%. Leadless system pacing was preferred over conventional pacing in pts with: transvenous pacemaker extractions due to infectious 18.5% or vascular 1.5% complications; active systemic infection and urgent need for cardiac stimulation 20%; complex conventional vascular approach 21.6%; severe tricuspid valve disease 1.5%; deterioration of general condition and clinical frailty 22.3%; shortly after transvalvular aortic valve replacement 8.5%. Among the pts, 6.2% had previous leadless Nanostim® device implantation with dysfunction of the system. Pts had either local anesthesia 13.2% or deep sedation 86.8%. The average fluoroscopy time was 4.3±2.9 minutes and number of device deployments before the final position ranged from 1 to 7 with a mean value of 1.5±1 positions. Pacing threshold during implant was 0.5±0.4 V at 0.24ms, only 4 pts (3%) had an implant threshold of >1.0 V at 0.24 ms. Two postoperative deaths were observed: 1 cardiac arrest related to myocardial dysfunction and consequent pulmonary edema in a patient with advanced heart failure, and 1 death secondary to myocardial perforation with need for surgical repair that occurred among the first implantations with an apical device position and a patient with multiple comorbidities. The total rate of major complications was 2.3% with only 1 vascular complication at the femoral puncture site. The median time from the leadless pacemaker implant procedure to discharge was 5±6.5 days (minimum 1 and maximum 40 days): 55.6% pts were able to leave the cardiology department within the first 72 hours. The mean FU period was 17 months ± 15 months with a mortality rate of 12.3% (cardiovascular impairment 5.4%; non cardiovascular-related deaths 6.9%). Increase in pacing thresholds was noted in 4 pts with subsequent stabilization; 92.2% of pts presented with thresholds lower than 1V at 0.24 ms. All pts remained free of infections during FU with no cases of device dislodgement observed. Conclusion: Elderly pts are at higher risk of complications; our experience confirms their clinical frailty and underlines the favorable safety profile of leadless system pacing with a low rate of complications and stable pacing thresholds.